How School Management Committees monitor the implementation of Universal Primary Education in Uganda - Ogina, Teresa Auma (University of Pretoria, 2018)
The provision of basic education through the UPE programme has gained momentum since its inception. This is because since the government took over the roles of paying tuition fee, providing instructional materials, paying teachers and providing school infrastructure, enrolment rose, and has continued to rise. In ensuring that government resources are well utilised, the government mandated the community through SMCs and charged them with the responsibilities of mobilising school resources from the community to supplement government resources that are insufficient for schools, monitoring the utilisation of school resources and undertaking general management roles in schools to ensure that there is efficient education service delivery that promotes teaching and learning. The purpose of this study was, therefore, to explore how SMCs monitor the implementation of UPE in Uganda. The study was driven by the assumption that if school resources are effectively monitored by the community themselves through SMCs, the government‘s objective of ensuring that all school-going children access school could be realized. The study used an explanatory sequential mixed methods approach to conduct a comprehensive study that gave a clear understanding of how monitoring the school resources is effected. Simple random sampling was used to select the sample for the quantitative study and data was collected using a questionnaire while purposive sampling was used to select the participants for the qualitative study and data was collected using structured interview.The result of the study identified the gaps in the way in which the SMCs monitor the school resources. The study results indicate that the SMCs do not have the full mandate to take any decisions that affect the operations of schools. This acts as a demotivating factor to SMCs in undertaking their roles. The study findings further reveal that there is no clear monitoring framework used by SMCs that guides them on what to monitor and how to monitor based on set measurable indicators. This gap leaves the SMC in each school to undertake their duties differently, yet they monitor the same programme. The study further reveal that SMCs encounter challenges in effecting their work; some of these challenges are policy issues and others are administrative in nature. Much as the they have attempted to come up with strategies to handle the challenges, little is being done to address them. The study findings have implications for policy-makers and UPE implementers. The study recommends that the Central Government should consider empowering SMCs through constant training in financial management and understanding policies governing their duties and responsibilities. The study further recommends that for UPE policy of community management of schools to be ffective, Government should put in place the level of education and experience for some one to be elected as a member of SMC.